2020
DOI: 10.14744/tjtes.2020.59680
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Tick Detachment Techniques and Technical Mistakes Made During Tick Removal

Abstract: BACKGROUND: Tick is among the important ectoparasites of humans and animals. Ticks may transmit disease-causing pathogens to humans. Tick contact may be resulted in several viral and bacterial infections, including Crimean-Congo Hemorrhagic Fever. Timely removal of ticks with appropriate methods is important in prevention of disease transmission. There are many methods reported for tick detachment. In this study, we aimed to evaluate two of them, suture lassoing and freezing and to compare both methods and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Three RCTs [401][402][403] and 5 observational studies [404][405][406][407][408] were identified, 2 of which were not in the original (adoloped) SysRev. 404,407 For the critical outcome of tick (or tick part) removal and the important outcome of damaged or broken-off mouthparts, an overview of studies, certainty of evidence, and key outcomes are presented in Table 18.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Three RCTs [401][402][403] and 5 observational studies [404][405][406][407][408] were identified, 2 of which were not in the original (adoloped) SysRev. 404,407 For the critical outcome of tick (or tick part) removal and the important outcome of damaged or broken-off mouthparts, an overview of studies, certainty of evidence, and key outcomes are presented in Table 18.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…If one cannot remove the Ixodes by itself, a doctor should help with the procedure. The study of Şahin et al shows that about 77% of the bitten patients had their tick removed by healthcare workers [42]. In the current study, the respondents usually stated that the correct technique for tick-removal was to wring it off the skin clockwise.…”
Section: Discussionmentioning
confidence: 60%
“…A group of Turkish researchers noted that the majority of ticks attached to the patients admitted to the investigated emergency department were removed by healthcare professionals (77.4%), while 22.6% of patients removed them themselves by hands [24]. Ticks crushed and broken off due to the technical mistakes during removal were more commonly seen in patients attempting self-removal without professional help [23].…”
Section: оригінальні дослідження загальна хірургіяmentioning
confidence: 99%
“…Generally speaking, ticks must be removed as early as it is safely possible, once they are discovered [21,22]. Meth- [6,8,23], which can be implemented either by patients themselves or by medical professionals (general surgeons) or healthcare practitioners at the local trauma centers [18,21].…”
Section: Introductionmentioning
confidence: 99%